PENGARUH PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI MINI MARKET CAHYA 99 DI DESA GONILAN KARTASURA - Hartanto, Lius; Putra, Ghanim Permana; Arinta, Deva Novia; Enjarwati, Aliffia Ori; Ramadhan, Viona Rizky; Rahadhini, Marjam Desma (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this study is to find out about the effect of perceived price and service quality on purchasing decisions. This research was conducted at the cahya 99 mini market in Gonilan Kartasura Village, by distributing questionnaires to 30 respondents. Samples were taken using random sampling technique. From the results of this study it is known that the regression equation is 10.288+0.462X1+0.083X2. From the results of statistical analysis data, the indicators in this study are said to be valid and reliable. The variable that has the most dominant influence is the price perception variable with a coefficient of 0.462. While the least influential variable is the service quality variable with a regression coefficient of 0.083. The price perception variable with a calculated T value of 3.620 with a significant value of 0.003 (0.003 <0.05) which means it has a significant value and for service quality obtains a T test result of 0.764 with a significant value of 0.05 (0.452 <0.05 ) which means it has a significant value. So it can be concluded that the perception of price and service quality has an effect on purchasing decisions at the cahya 99 mini market in Gonilan Kartasura Village. Perceptions of price and service quality are key strategic roles that are important to be considered in purchasing decisions at the Cahya 99 Minimarket in Gonilan Kartasura Village.